Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 11 - Infinite Series - 11.1 Sequences - Exercises - Page 538: 64



Work Step by Step

When $\lim\limits_{x \to \infty} f(x)$ exists then the sequence $a_n=f(n)$ converges to the same limit, so we have: $ \lim\limits_{n \to \infty} a_n=\lim\limits_{x \to \infty} f(x)$ Now, $ \lim\limits_{n \to \infty} a_n=\lim\limits_{x \to \infty} \dfrac{\ln (1+\dfrac{1}{x} )^2}{1/\sqrt x} $ We see that this limit shows the indefinite form of $\dfrac{0}{0}$, so we apply L-Hopital's rule. Thus, $ \lim\limits_{n \to \infty} a_n =-2 \lim\limits_{x \to \infty} \dfrac{x^{3/2} }{x^2 (1+\dfrac{1}{x})} \\=-2 \lim\limits_{x \to \infty}\dfrac{1}{(1+\dfrac{1}{x})} \cdot \lim\limits_{x \to \infty} \dfrac{1}{\sqrt x}\\= -2 \dfrac{\lim\limits_{x \to \infty} (1)}{\lim\limits_{x \to \infty} (1+\dfrac{1}{x})} \cdot \lim\limits_{x \to \infty} \dfrac{1}{\sqrt x}\\=0 $
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.